Microgel particle-laden drop impact on a nanofiber material with varying wettability: Effect of liquid impalement; Physics of Fluids; Vol. 36, iss. 10 - Piskunov M. V. Maksim Vladimirovich; Piskunova A. E. Aleksandra Evgenjevna; Ashikhmin A. E. Alexander Evgenjevich; Melnik E. Yu. Evgeniy Yurjevich; Bolbasov E. N. Evgeny Nikolaevich (2024, 2024)
Title screen